2007
DOI: 10.1111/j.1365-2524.2007.00701.x
|View full text |Cite
|
Sign up to set email alerts
|

The Expert Patients Programme: a paradox of patient empowerment and medical dominance

Abstract: Self-care is seen as a key element in managing resource demand in chronic disease and is also perceived as an empowering right for patients. The Chronic Disease Self-Management Programme developed in the USA has been adopted in a number of countries and in the UK has been as adapted as the Expert Patients Programme. However, despite its potential as a lay-led empowering initiative, the Expert Patients Programme has been criticised as perpetuating the medical model and failing to reach those in most need. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
121
0
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(129 citation statements)
references
References 68 publications
2
121
0
6
Order By: Relevance
“…The dietician also provided menu suggestions to the patients. Group discussions and sharing the experience of "expert patients" were also used as previous studies found that information is more effectively transferred to and accepted by patients through group communication 9 than by oral education given by medical staff. 10 Group education can help patients to control their protein intake and can help them to achieve other important lifestyle changes that are beneficial for disease therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The dietician also provided menu suggestions to the patients. Group discussions and sharing the experience of "expert patients" were also used as previous studies found that information is more effectively transferred to and accepted by patients through group communication 9 than by oral education given by medical staff. 10 Group education can help patients to control their protein intake and can help them to achieve other important lifestyle changes that are beneficial for disease therapy.…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing body of evidence that involvement in care leads to improved health outcomes 53,54 and patient experience, 55,56 but less evidence on any impact of PPI on the planning and commissioning of health services. 57 Within the health research arena, the policy approach to PPI has been underpinned by various claims regarding the impact of PPI.…”
Section: Patient and Public Involvement: The Methodological Argumentmentioning
confidence: 99%
“…46 Training needs to be informed by research. Our study fi ndings point to the need for using direct observation of primary care consultations with patients who have CFS/ME to test our hypothesis that patients and family physicians present their knowledge about CFS/ ME using scientifi c discourse, to explore the reasons why they do so, and to determine whether it leads to a satisfactory understanding of CFS/ME for both patient and physician.…”
Section: Training Issuesmentioning
confidence: 99%